(untitled) (Revista de Estudios Europeos, 2026)
Between 2003 and 2005, the member states of the European Union (EU) faced significant internal discord due to the Iraq War. While some countries, such as the United Kingdom and Spain, endorsed the U.S.-led military intervention, others, like Germany and France, strongly opposed it. This study delves into the underlying motivations that shaped the decisions of these four nations. It explores whether the primary driving force was the Franco-German axis’s commitment to upholding "international legality" in opposition to the Anglo-Saxon interventionist approach, which was supported by Spain.